Esclerose sistêmica: aspectos epidemiológicos, características clínicas e manifestações orofaciais na região oeste do Paraná - Balbinot, Alana Rubia (2021)
Systemic sclerosis (SS) is a chronic and heterogeneous disorder, usually characterized by vascular, inflammatory and fibrotic changes in the skin and in several internal organs due to dysfunction of three main elements: fibroblasts, endothelial cells and the immune system. These changes result in the obliteration of microvessels, collagen buildup leading to skin tightening and damage to the gastrointestinal tract, kidneys, lungs, heart and oral cavity. Epidemiological studies in Brazil regarding systemic sclerosis are scarce and reports on orofacial changes, the vast majority, come from the international literature. The objective of this study was to determine the incidence and prevalence, clinical, laboratory tests, therapeutic approach and orofacial manifestations of all patients diagnosed with SSc in the western region of Paraná. Data were collected from August 2019 to August 2020 in six private rheumatology clinics, in a regional specialty center, in the municipal specialty center and in the specialty clinic of the Hospital Universitário do Oeste do Paraná. After the epidemiological survey, those chosen were chosen to participate in the investigation of possible orofacial manifestations, such as: hyposalivation, presence of telangiectasia, microstomy, presence of caries and periodontal disease. A survey identified 57 (100%) patients diagnosed with SSc in the western region of Paraná, and of these, 30 (52,63%) were residents of Cascavel/PR. This allowed the calculation of the incidence, estimated at 1.2 cases/100,000 inhabitants/year, using the one diagnosed in the year of the survey, while the prevalence (prevails with all patients) was 9 cases /100,000 inhabitants. Most patients were female (90%) and the mean age was 42.5 ± 17.22 years. The most frequently reported clinical feature was Raynaud's phenomenon (86.67%), followed by skin thickening (70%). The limited SS was more identified by physicians (60%) and the ANA exam responded in 86.66% of the cases. In the investigation of orofacial changes, six patients agreed to participate. Of these, 50% had very low hyposalivation, all of which had telangiectasias and periodontal disease. Of those that allowed evaluation of mouth opening, 50% were considered microstomes. The CPO-d index was 21.16, while the mean plaque and dental calculus index were 0.37 and 0.23, respectively. This study emphasizes and confirms the importance of epidemiological studies of autoimmune diseases and that despite possible biases, the data found are in agreement with other parts of the world. Higher education presents a great challenge for physicians and dentists, in terms of diagnosis and impact on oral health and quality of life, requiring further investigations and a larger sample.